Sexual and Reproductive Health Needs of HIV-Positive People in Tehran, Iran: A Mixed-Method Descriptive Study - Saharnaz Nedjat; Babak Moazen; Farimah Rezaei; Shayesteh Hajizadeh; Reza Majdzadeh; Hamid Reza Setayesh; Minoo Mohraz; Mohammad Mehdi Gooya (International Journal of Health Policy and Management, 2015)
Background People Living with HIV (PLHIV) are highly stigmatized and consequently hard-to-access by researchers and importantly, public health outreach in Iran, possibly due to the existing socio-cultural situation in this country. The present study aimed to evaluate the sexual and reproductive health needs of PLHIV in Tehran, the capital of Iran.